Online Quantification of Lactate Concentration in Microdialysate During Cerebral Activation Using 1H-MRS and Sensitive NMR Microcoil - Crémillieux, Yannick; Dumont, Ursule; Mazuel, Leslie; Salvati, Roberto; Zhendre, Vanessa; Rizzitelli, Silvia; Blanc, Jordy; Roumes, Hélène; Pinaud, Noël; Bouzier-Sore, Anne-Karine (Frontiers in Cellular Neuroscience, 2019)
The dynamic in vivo profiling of lactate is of uppermost importance in both neuroenergetics and neuroprotection fields, considering its central suspected role as a metabolic and signaling molecule. For this purpose, we implemented proton magnetic resonance spectroscopy (1H-MRS) directly on brain microdialysate to monitor online the fluctuation of lactate contents during neuronal stimulation. Brain activation was obtained by right whisker stimulation of rats, which leads to the activation of the left barrel cortex area in which the microdialysis probe was implanted. The experimental protocol relies on the use of dedicated and sensitive home-made NMR microcoil able to perform lactate NMR profiling at submillimolar concentration. The MRS measurements of extracellular lactate concentration were performed inside a pre-clinical MRI scanner allowing simultaneous visualization of the correct location of the microprobe by MRI and detection of metabolites contained in the microdialysis by MRS. A 40 % increase in lactate concentration was measured during whisker stimulation in the corresponding barrel cortex. This combination of microdialysis with online MRS/MRI provides a new approach to follow in vivo lactate fluctuations, and can be further implemented in physio-pathological conditions to get new insights on the role of lactate in brain metabolism and signaling.